Urethral Stricture Formation Following Cuff Erosion of AMS Artificial Urinary Sphincter Devices: Implication for a Less Invasive Explantation Approach - Kuhlencord, Katharina; Dahlem, Roland; Vetterlein, Malte W.; Abrams-Pompe, Raisa S.; Maurer, Valentin; Meyer, Christian P.; Riechardt, Silke; Fisch, Margit; Ludwig, Tim A.; Marks, Phillip (Frontiers in Surgery, 2022)
Objectives The objective of this study is to describe a standardized less invasive approach in patients with artificial urinary sphincter (AUS) explantation due to cuff erosion and analyze success and urethral stricture rates out of a prospective database. Evidence regarding complication management is sparse with heterogenous results revealing high risk of urethral stricture formation despite simultaneous urethroplasty in case of AUS explantation. Patients and Methods Data of all patients undergoing AUS implantation due to stress urinary incontinence (SUI) in our tertiary center were prospectively collected from 2009 to 2015. In case of cuff erosion, AUS explantation was carried out in an institutional standardized strategy without urethroplasty, urethral preparation or mobilization nor urethrorrhaphy. Transurethral and suprapubic catheters were inserted for 3 weeks followed by radiography of the urethra. Further follow-up (FU) consisted of pad test, uroflowmetry, postvoiding residual urine (PVR), and radiography. Primary endpoint was urethral stricture rate. Results Out of 235 patients after AUS implantation, 24 (10.2%) experienced cuff erosion with consecutive explantation and were available for analysis. Within a median FU of 18.7 months after AUS explantation, 2 patients (8.3%) developed a urethral stricture. The remaining 22 patients showed a median Qmax of 17 ml/s without suspicion of urethral stricture. Median time to reimplantation was 4 months (IQR 3-4). Conclusion We observed a considerably low stricture formation and could not prove an indication for primary urethroplasty nor delay in salvage SUI treatment possibilities. Therefore, the presented standardized less invasive explantation strategy with consequent urinary diversion seems to be safe and effective and might be recommended in case of AUS cuff erosion.